COVID-19 and Labor Shortage in France: Exploring the Contribution of Tunisian Migrant Workers in bridging the Labor Shortage - Gasmi, Sana (AUC Knowledge Fountain, 2024)
This thesis employed a qualitative approach, combining both desk research and in-depth interviews with 11 participants: nine Tunisian migrant workers and two Tunisian migrant experts. The thesis examined labor shortage in France during the pandemic and the extent to which Tunisian migrant workers managed to bridge the labor shortage relying on the Segmented Labor market theory which was originally developed by Piore (1979), and the two concepts: System Effects and Systemic Resilience. Findings indicate that the COVID-19 pandemic unveiled several weaknesses in the French labor market system including the acute labor shortage. Faced by labor shortage, France turned to migrant workers to meet its labor demand which became problematic with border closures. Tunisian migrant workers, the focus of this thesis, contributed to bridging the labor shortage in France. They actively participated in labor shortage affected occupations and in essential occupations. Findings indicate that due to the high labor demand which was experienced in the French labor market during the COVID-19 pandemic , Tunisian migrant workers who worked in essential occupations had facilitated recruitment procedure while the Tunisian migrant workers who worked in non-essential occupations had an accustomed recruitment procedure. Findings also highlight that migrant workers including Tunisian migrant workers contributed to building systemic resilience in France through offering flexibility in terms of employment and supporting the growth of networks that facilitate meeting the labor demand.